Molecular dynamics of carboxymethyl κ/ι-hybrid carrageenan films doped with NH4I. Issue 8 (24th May 2019) - Torres, Fernando G.; Arroyo, Junior; Alvarez, Ricardo; Rodriguez, Sol; Troncoso, Omar; López, Daniel
ABSTRACT: The effect of carboxymethylation and NH4 I incorporation on the molecular dynamics of carrageenan films was studied. Broadband Dielectric Spectroscopy (BDS) assessed the presence of α and β relaxation processes. The effect of NH4 I content was analyzed using the Havriliak-Negami model and parameterizing the temperature dependence of the relaxation times according to the Vogel-Fulcher-Tammann-Hesse (VFTH) equation. The glass transition temperature was found to decrease with the increase of NH4 I content. These results suggest that carboxymethylation and the salt doping treatment increase the molecular mobility of NH4+ ions, making the films suitable for the development of solid electrolytes for energy storage applications. Graphical Abstract: